Penerapan Pewarnaan Graf pada Pembagian Kamar Asrama Mahasiswi Universitas Mataram dengan Algoritma Welch Powell - Ratih Dhamayyana Dwi Cinthami; Sudi Prayitno; Gilang Primajati (Mandalika Mathematics and Educations Journal, 2025)
Room assignments at the female dormitory of Universitas Mataram are still done manually, often placing students from the same study program and semester in the same room. This condition limits academic diversity, which is essential to foster social interaction and enhance academic performance. This study aims to apply graph coloring theory to address this issue. Each student is represented as a vertex, and connections between students with the same academic background are represented as edges. The Welch Powell algorithm is applied to color the vertices so that no adjacent vertices share the same color, ensuring students with similar academic characteristics are not assigned to the same room. This applied research uses Visual Basic for Applications (VBA) Macro in Microsoft Excel to automate the creation of matrices and implementation of the algorithm. The results show that this approach is effective and efficient in grouping students into rooms while promoting academic heterogeneity. This method is expected to serve as a practical solution for dormitory management in other higher education institutions.